Intraluminal high‐dose‐rate brachytherapy for palliation of dysphagia in cancer of the esophagus: initial experience at a single UK center. Issue 1 (9th March 2012) - Bhatt, L.; Tirmazy, S.; Sothi, S.
SUMMARY Esophageal cancer tends to present with advanced disease, and the majority of patients are suitable only for palliative treatment at diagnosis. Dysphagia is the most common presenting symptom and significantly undermines quality of life. High‐dose‐rate intraluminal brachytherapy (ILBT) has been an option for the palliation of dysphagia for many years and has been used at our center since 2006. Experience was presented in terms of improvement of dysphagia and survival. Patients were identified from the local radiotherapy database. Original treatment sheets and clinical notes were reviewed retrospectively to obtain treatment details, pretreatment and post‐treatment dysphagia scores, and survival information. Between January 2006 and January 2010, 21 patients of median age 77 years with a mean pretreatment dysphagia score of 2.5 underwent ILBT for esophageal cancer. All received 12 Gy in a single fraction. Thirteen (62%) had adenocarcinoma and eight (38%) squamous cell carcinoma. Four (19%) tumors were in the mid‐esophagus and 17 (81%) in the lower esophagus. Eight had extension of tumor into the gastroesophageal junction. Seven patients (33%) received chemotherapy as first‐line treatment prior to brachytherapy. Nineteen patients had clear documentation of dysphagia scores both pretreatment and post‐treatment, and the improvement overall was significant (P= 0.04). Ten patients (53%) had an improvement in dysphagia score. Five of these (50%) went on to require further endoscopic intervention due to disease progression. Median duration of response was 4 months. Of the nonresponders, six (67%) went on to require further endoscopic intervention. No patients experienced documented toxicity aside from a short‐lived acute esophagitis. Median survival from date of diagnosis was 12 months and from treatment date was 5 months (1–32 months). In our series of elderly patients with significant dysphagia, ILBT was a well‐tolerated and effective treatment. It should be considered as a palliative option in esophageal cancer.